Blockchain-based Trusty Buyer Coalition Scheme Using A Group Signature - Laor Boongasame; Supansa Chaising; Punnarumol Temdee (My University, 2021)
Without trust, buyers may not join a coalition. Despite the tremendous need for trustworthy relationships in buyer coalitions, no current buyer coalition scheme explicitly tackles confidence issues with blockchain technology. This study proposes an algorithmic design, the blockchain-based trusty buyer coalition scheme, to satisfy the trust requirement among different actors while forming the coalition. All activities forming a coalition through a decentralized public ledger can be explicitly examined. Consequently, the proposed algorithm can ensure anonymity within a community, resulting in trusting relationships. Furthermore, the proposed algorithm can ensure correctness and accountability by recognizing misbehavior and enforcing alternative forms of punishment. Additionally, the discovered algorithm can be applied to mobile commerce applications.
Keywords: Group signature; Trustworthiness; Ledger; Punishment (psychology); Blockchain Technology Applications and Security